Reduced filaggrin expression is accompanied by increased Staphylococcus aureus colonization of epidermal skin models. Issue 12 (December 2014) - van Drongelen, V.; Haisma, E. M.; Out‐Luiting, J. J.; Nibbering, P. H.; El Ghalbzouri, A.
Summary Background Atopic dermatitis is an inflammatory skin disease that is characterized by a reduced skin barrier function, reduced filaggrin (FLG) expression as well as increased colonization by Staphylococcus aureus. Objective This study focused on the possible involvement of FLG in epidermal colonization by S. aureus and/or whether it affects the epidermal defence mechanisms, including the expression of antimicrobial peptides (AMPs) and enzymes involved in stratum corneum barrier lipid synthesis. Furthermore, IL‐31 has been shown to reduce FLG expression, but its effects on bacterial colonization and on the expression of AMPs and enzymes involved in the barrier lipid synthesis are not known. Material and Methods We established N/TERT‐based epidermal models (NEMs), after FLG knockdown (FLG‐KD) and/or cultured with IL‐31, that were colonized with S. aureus for 24 h. Results Both FLG‐KD and IL‐31 supplementation resulted in significantly increased epidermal S. aureus colonization, as well as in an up‐regulation of S. aureus‐induced IL‐8 expression. IL‐31, but not FLG‐KD, prevented S. aureus‐induced up‐regulation of mRNA expression for the AMPs human β‐defensin 2 and ‐3 and RNAse7, whereas psoriasin expression remained unchanged. Furthermore, the S. aureus colonization induced changes in mRNA expression of ELOVL4 was not affected by FLG‐KD, but was blocked by IL‐31. Expression of SCD‐1 and Gcase mRNA was reduced by IL‐31, but not by FLG‐KD. Conclusion This study shows that NEMs, with FLG‐KD and/or cultured in the presence of IL‐31, mimic the skin of patients with atopic dermatitis in several aspects, including enhanced bacterial colonization, increased inflammatory and reduced protective responses.